2006
DOI: 10.1080/02770900600758309
|View full text |Cite
|
Sign up to set email alerts
|

Association of Excess Weight and Degree of Airway Responsiveness in Asthmatics and Non-Asthmatics

Abstract: It is unclear whether obesity is associated with increasing degree of airway responsiveness in asthmatics. In this study, methacholine challenge test results of 1,725 subjects with respiratory symptoms were reviewed. Obesity was associated with asthma with an odds ratio of 1.72 (95% C.I. 1.36, 2.17). Although there was a significant difference in the degree of airway responsiveness between various body mass index categories of non-asthmatics (p = 0.01), no significant difference was noted among asthmatics (p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…In an earlier report, BMI was negatively correlated with the presence of AHR confirmed by MBPT [11], and others have reported that obesity is a risk factor for asthma and wheezing, but not for AHR [2,8,9,10,11,20,21]. However, many studies have shown a link between obesity and increases in both AHR and the prevalence of asthma in the general population [4,5,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier report, BMI was negatively correlated with the presence of AHR confirmed by MBPT [11], and others have reported that obesity is a risk factor for asthma and wheezing, but not for AHR [2,8,9,10,11,20,21]. However, many studies have shown a link between obesity and increases in both AHR and the prevalence of asthma in the general population [4,5,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…In studies assessing obesity and asthma, the definition of asthma is critical because obesity can mimic asthma by causing wheezing [10,24,25]. Studies in asthmatic patients have consistently shown no relationship, or even a negative association, between obesity and AHR [2,8,9,10,11]. It is inferred that obesity has different effects on AHR in asthmatic individuals compared with non-asthmatic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin levels increase with obesity, resulting in a subsequent upregulation of pro-inflammatory cytokine production (Sood et al, 2006). Contrarily, obesity-related decrease in adiponectin levels can negatively regulate allergic airway inflammation (Shore et al, 2006).…”
Section: Asthma and Airway Inflammationmentioning
confidence: 99%
“…A recent meta-analysis of a prospective epidemiologic study demonstrated a clear dose-response relationship between body mass index (BMI) and incident asthma [2]. Obesity has also been associated with airway hyperresponsiveness [3][4][5] and reduced response to asthma medication [6,7]. Moreover, intervention consisting of weight reduction in obese asthmatics improved morbidity, lung function and the number of exacerbations [8].…”
Section: Introductionmentioning
confidence: 99%